2008
DOI: 10.1016/j.juro.2007.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum A Toxin Intravesical Injection in Patients With Painful Bladder Syndrome: 1-Year Followup

Abstract: Intravesically injected botulinum toxin A is effective for short-term management of refractory painful bladder syndrome. The beneficial effects decreased progressively within a few months after treatment. Thus, repeat injections of the neurotoxin are required for efficacious treatment in patients with the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 18 publications
2
76
1
4
Order By: Relevance
“…As far as the long-lasting results of resiniferatoxin are concerned, the beneficial effects reported by the reviewed studies were still present, though decreased, at the 12-week follow-up end points. The same is true about another treatment option: intravesical administration of botulinum toxin type A. Giannantoni et al [30], in a recent study, concluded that this regimen was effective for short-term management of refractory interstitial cystitis and that the beneficial effects decreased progressively within a few months after treatment.…”
Section: Discussionmentioning
confidence: 98%
“…As far as the long-lasting results of resiniferatoxin are concerned, the beneficial effects reported by the reviewed studies were still present, though decreased, at the 12-week follow-up end points. The same is true about another treatment option: intravesical administration of botulinum toxin type A. Giannantoni et al [30], in a recent study, concluded that this regimen was effective for short-term management of refractory interstitial cystitis and that the beneficial effects decreased progressively within a few months after treatment.…”
Section: Discussionmentioning
confidence: 98%
“…In a prospective study of effect of botulinum toxin A in painful bladder syndrome, at 1 year follow up, it was seen that the beneficial effect lasted at 3 months in 86% and 30% at 5 months. There was a significant decrease in pain, accompanied by increase in maximum cystometric capacity and in day time and night time urinary frequency, but after 1 year pain had recurred in all, requiring repeat injection [51]. However, this requires confirmation by a randomized placebo controlled study.…”
Section: Urinary Bladder Dysfunctionmentioning
confidence: 93%
“…Giannantoni et al (36) reported that 200 IU BoNT-A injected into the detrusor muscle in patients with BPS provided significant improvement in pain, urinary frequency, voided volume, and bladder capacity; however, all patients had recurrent basal complaints at the end of the first year. In a randomized controlled trial including 67 patients (56 females, 11 males) by Kuo and Chancellor (37), BoNT-A injections (100 IU and 200 IU) with or without hydrodistension were compared.…”
Section: -Interstitial Cystitis/bladder Pain Syndromementioning
confidence: 99%